Peer review of the pesticide risk assessment of the active substance buprofezin - European Food Safety Authority (EFSA); Fernando Álvarez; Maria Arena; Domenica Auteri; Sofia Batista Leite; Marco Binaglia; Anna Federica Castoldi; Arianna Chiusolo; Angelo Colagiorgi; Mathilde Colas; Federica Crivellente; Chloe De Lentdecker; et al. (EFSA Journal)
Abstract The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State Italy and co‐rapporteur Member State Austria for the pesticide active substance buprofezin. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of buprofezin as an insecticide on ornamental plants in greenhouse via spray application. The reliable end points, appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.